Socioeconomic factor and satisfaction of MCH client in urban slum of Meerut, Uttar Pradesh - Singh, Nripendra; Jain, Seema; Chopra, Harivansh; Kumar, Arun; Singh, Ganesh; Kesarwani, Priyanka (International Journal Of Community Medicine And Public Health, 2017)
Background: The health of the mother and child constitutes one of the most serious health problems affecting the community, particularly in the developing countries like India. Promotion of maternal and child health has been one of the most important aspects. But any program, however, relevant its components were likely to fail unless it succeeds in improving the knowledge and achieving satisfaction of its respondent. Client satisfaction has traditionally been linked to the quality of services given and the extent to which specific needs were met. The objective of the study was to determine the level of satisfaction and correlated factor among mothers visiting primary health care institutions for maternal care services. Methods: A cross sectional study was carried out on 384 women attending 19 urban health post located in Meerut. Results: In present study 76.0% MCH respondent belong to lower socioeconomic class, 46.4% MCH respondent were 6-12th class pass, 33.1% MCH respondent belong to SC/ST category. Satisfaction with behavior of staff was significant associated with socioeconomic class, educational qualification and religion of respondent. Satisfaction with cleanliness is significantly associated with socioeconomic status, type of family, education and caste of client. Satisfaction with availability of drug is significantly associated with socioeconomic status, education, category and religion of respondent. Satisfaction with behavior of doctor is significantly associated with type of family, education and category of respondent. Conclusions: In present study, we observed that satisfaction of MCH respondents were closely related to the services provided at MCH center and with the behavior of health care providers.